The world in 24 pages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Who owes who? Christian Aid, London. 1999. 24 pp. £ 3.50 E 5.40 Christian Aid 35 Lower Marsh London, SE1 7RL UK Fax: + 44 20 7620 0719